Effect of isolated facial feature transformations in a change blindness experiment involving a person as the object of change - Kadosh, Hadar (My University, 2008)
Research has shown that people often fail to notice changes to visual scenes. This phenomenon is known as change blindness. This study investigated the effect of facial feature transformations on change blindness using change detection tasks involving a person as the object of change. 301 participants viewed a photo-story comprised of a few still frames. In the final frame, a selected facial feature of a character in the story was altered. Four different photo-stories were used, each utilising a different alteration. Questionnaires designed to determine whether the change was detected were administered. Results showed that changes to facial features considered to be more salient produced higher levels of change detection. A flicker test using the same images from the photo-story was administered to a further 75 participants and showed a similar pattern of results. It was concluded that in order to detect change, the changing stimuli have to be both salient and meaningful.
Keywords: change blindness; change detection; visual perception; attention; memory; facial features; cue salience